Research on functional constipation with anxiety or depression: a bibliometric analysis - Li, Xiaoqin; Lei, Qiang; Xie, Jiao; Li, Fang; Liu, Jing; Chen, Yuelai; Mao, Qiangjian (Frontiers in Psychiatry, 2025)
BackgroundAlthough the phenomenon of functional constipation (FC) that accompanies anxiety or depression has been extensively investigated worldwide, no bibliometric studies are available in this regard. This study therefore aimed to analyze the current status and extent of research and areas of interest in the study of FC with anxiety or depression.MethodsData from studies on FC with anxiety or depression, that were performed between 2003 and 2024, were retrieved from the Web of Science Core Collection database. Data regarding the annual number of publications, authors, countries, and references were assessed using CiteSpace v6.3.R1 (64-bit) and Microsoft Excel, and those pertaining to keywords and cited authors were evaluated using VOSviewer 1.6.20. The co-occurrence and clustering functions were then used to generate visual knowledge maps.ResultsThe overall annual publication volume demonstrated an upward trend between 2003 and 2024; this was indicative of promising research prospects. The 427 publications identified included 6 types of papers, among which original research articles represented the highest proportion (357 [83.61%] articles published across 200 journals). Neurogastroenterology and Motility had the highest publication volume (30 articles, 7.02%). The United States of America had published most of the papers (135 articles, 31.61%) on the topic. Harvard University was the research institution with the most published papers (21 articles, 4.92%), and Michel Bouchoucha had authored the highest number of articles (13 articles, 3.04%).ConclusionFuture studies in the field of basic medicine need to determine the etiology and pathogenesis of FC with anxiety or depression; in particular, they need to evaluate the role of opioid drugs as a key etiological factor. The role played by the brain-gut axis also warrants investigation. From the clinical perspective, studies need to focus on evidence-based medicine; particular emphasis needs to be placed on randomized double-blind controlled trials with stringent quality control, high-quality meta-analyses, and evaluation of questionnaires and scales. Treatment techniques need to be explored in greater detail; in this context, it is recommended that fecal microbiota transplantation and biofeedback therapy are adopted in the clinic. Furthermore, Patients with FC, especially those with a history of anxiety or depression, tend to have overlapping dyspepsia symptoms.